The Worlds of Langston Hughes Modernism and Translation in the Americas - Kutzinski, Vera M. (Cornell University Press, 2012)
Shortlisted for the Phi Beta Kappa Society's Christian Gauss Award.The poet Langston Hughes was a tireless world traveler and a prolific writer, translator, and editor. Translations of his own writings traveled even more widely than he did, earning him adulation throughout Europe, Asia, and especially the Americas. This study contends that, for writers who are part of the African diaspora, translation is more than just a literary practice: it is a fact of life and a way of thinking. "Kutzinski has given us one of the very best analyses and evaluations of Hughes's seminal texts. We observe him at work translating, but we also see his works being translated. Kutzinski, a preeminent polylingual comparativist who knows the literatures of the African diaspora as well as anyone, brings a keen understanding of both race and ethnicity to her overarching discussion. She has written an exemplary work, which will be widely influential."-John Lowe, Louisiana State University